Nutritional supplement in malnutrition elderly subjects - Fernandes,Elci Almeida (2008)
Considering the difficulty that some people have in the intake of adequated quantities of food that fit their nutritional needs, the supplement prescription has been done in order to correct nutritional deficiency manifestation and to assure adequate food intake by a person with insufficient diet on macro and micronutrients. This study has been based on literature researches about the nutritional supplement embracing the period from 1987 to 2006, intending to identify its use on several clinical events. It was evidenced that nutritional supplement use increases according to age, being greater for women and for people with low Body Mass Index (BMI). Among the groups, elderly trends to greater food deficiency, and their health gets 2 or 3 time worse than the other groups. But about the hospitalized elderly it was verified that 40% of them are considered under nutrition and the clinical state recovery is influenced by the long hospitalization period, and mainly of these patients show weight reduction. In this sense, the nutritional supplement has been a satisfactory alternative that influences the nutritional treatment indication. The studies about the hospitalized elderly nutritional supplement consider taste, touch, appearance and variety as essential factors, as well as they show differences of application according to the different clinical events (chronic, pointed and cathabolic), seeking for the guarantee of use, acceptance and the product efficiency on each analyzed study.